2015
DOI: 10.1111/all.12703
|View full text |Cite
|
Sign up to set email alerts
|

Breast milk fatty acid composition has a long-term effect on the risk of asthma, eczema, and sensitization

Abstract: The association between breast milk fatty acid composition and asthma, eczema and sensitization persists up to the age of 14 years in children of both allergic and nonallergic mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 35 publications
2
55
1
Order By: Relevance
“…However, for mature breastmilk (2 weeks after delivery), total n ‐3 fatty acids and individual n ‐3 fatty acids (EPA, DHA, and DPA) were associated with reduced sensitization to food allergens (milk, egg, and peanut) at 12 months. These findings are supported by those of a separate study . A third study investigating the effects of maternal diet during lactation on the risk of sensitization to cow's milk, egg, wheat, and inhalant allergens in the offspring found none of the dietary variables investigated was significantly related to sensitization to milk or egg but was associated with sensitization to wheat.…”
Section: Role Of Fatty Acids In Food Allergysupporting
confidence: 55%
See 1 more Smart Citation
“…However, for mature breastmilk (2 weeks after delivery), total n ‐3 fatty acids and individual n ‐3 fatty acids (EPA, DHA, and DPA) were associated with reduced sensitization to food allergens (milk, egg, and peanut) at 12 months. These findings are supported by those of a separate study . A third study investigating the effects of maternal diet during lactation on the risk of sensitization to cow's milk, egg, wheat, and inhalant allergens in the offspring found none of the dietary variables investigated was significantly related to sensitization to milk or egg but was associated with sensitization to wheat.…”
Section: Role Of Fatty Acids In Food Allergysupporting
confidence: 55%
“…High levels of total n ‐6 PUFAs measured in breastmilk were associated with an increased risk for asthma‐like symptoms, whereas n ‐3 PUFAs decreased the risk of atopy . Similarly, asthma is less prevalent in children of allergic mothers receiving breastmilk with higher levels of n ‐3 LC‐PUFA and more prevalent in children of nonallergic mothers receiving breastmilk with higher levels of n ‐6 PUFA . However, another study suggested that maternal fatty acid intake during lactation did not influence the risk of asthma by 5 years of age …”
Section: Role Of Fatty Acids In Asthmamentioning
confidence: 99%
“…The three previous reports investigating the effects of breastmilk fatty acids on asthma included only high‐risk children of allergic mothers, or with allergic first‐degree family members, or provided only results stratified by maternal allergy . Although the overall sizes of our study populations are larger than those analyzed in previous studies, subjects in our cohort were recruited from the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the two previous reports on asthma stopping at four and seven years of age, in particular our analyses of late‐onset wheeze and asthma reflect long‐term health consequences. Further in contrast to the only report on long‐term associations with asthma, we investigated associations with time‐dependent patterns of wheeze rather than providing averaged effects by accounting for the correlation structure of repeated measurements of the outcome. Also unlike these studies, we were able to restrict analyses to exclusively breastfed infants for whom breastmilk was their only source of fatty acids during early postnatal life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation